Green cloud platform for flood early detection warning system in smart city - Yusoff A.; Mustafa I.S.; Yussof S.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cloud computing; Disasters; Flood control; Floods; Housing; Urban growth; Flood detections; Flood warning system; FMER; Green Clouds; Smart cities; Distributed computer systems